Climate diplomacy : new approaches for foreign policy - Adriázola, Paola [et al] (adelphi Research Gemeinnutzige GmbH BerlinDE, 2013)
Documents the political process and progress in Germany to engage stakeholders, partner countries and regional organisations on climate diplomacy. Highlights the achievements and key messages distilled from the joint initiative on climate change and security by the German Federal Foreign Office and adelphi.